miR-142-5p promotes cervical cancer progression by targeting LMX1A through Wnt/β-catenin pathway - Ke Lijuan (De Gruyter, 2021)
Previous work has shown that miR-142-5p in cervical cancer tissues increased significantly compared with adjacent normal tissues. However, the function and the mechanism of miR-142-5p in cervical cancer have not been reported.